STUDYING AND CALCULATION OF THE POTENTIAL ENERGY FOR TWO OF MOLECULES [TRIMETHYL GALLIUM AND TRIETHYL GALLIUM,] BY SEMI EMPIRICAL PROGRAMS - Abdul Rahman Rashid Hammood; Abdul Hakim shakkoor Mohammed; Nadim Khalid Hassan (Tikrit Journal of Pure Science, 2023)
In this research, the potential energy and vibration frequencies for two of an non-liner molecules [ (C3H9Ga) and (C6H15Ga)] have been studied and calculated by using the semi-empirical theoretical programs in method (MNDO/PM3) where the geometric space shape of two molecules has been calculated by using initial and final matrices that include bonds length, the angle between bonds, dihedral angles and the charge of each atom in the two molecules, which have been drawing a curved of potential energy per molecule where the drawing was adopted to change the length of the bond (Ga-C) in the each molecule compared to what is obtained from the values ​​of energy and it was total energy calculate  for each molecule at equilibrium distance was (-553.044 eV) at equilibrium distance (1.8327 ) and (-1003.53726 eV) at equilibrium distance (1.8344 ) for the two molecules, respectively, and from the carve of the potential energy  was the spectroscopy dissociation energy per molecule account it was equal to (4.508 eV) and (4.70991 eV) respectively .